2017
DOI: 10.3847/1538-3881/aa9b86
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Transit of the Earth-mass Exoplanet Proxima Centauri b in Antarctica: Preliminary Result

Abstract: ProximaCentauri is known as the closest star to the Sun. Recently, radial velocity (RV) observations revealed the existence of an Earth-mass planet around it. With an orbital period of ∼11 days, Proxima Centauri b is probably in the habitable zone of its host star. We undertook a photometric monitoring campaign to search for its transit, using the Bright Star Survey Telescope at the Zhongshan Station in Antarctica. A transit-like signal appearing on 2016 September 8 has been tentatively identified. Its midtim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…A planet in the habitable zone of Proxima Centauri was detected in Anglada-Escudé et al (2016) and confirmed recently in Damasso et al (2020) and Suárez Mascareño et al (2020). The planet, known as Proxima b, has not been observed as a transiting planet (Davenport et al 2016;Kipping et al 2017;Liu et al 2018;Blank et al 2018;Feliz et al 2019;Jenkins et al 2019) and the estimated geometric probability of a transit is about 1.5%, (Anglada-Escudé et al 2016). As a consequence, constraints can exclusively be set on the orbit semi-major axis and on the planet's revolution period, leaving mass, radius, and density of the planet to be assumed.…”
Section: Introductionmentioning
confidence: 66%
“…A planet in the habitable zone of Proxima Centauri was detected in Anglada-Escudé et al (2016) and confirmed recently in Damasso et al (2020) and Suárez Mascareño et al (2020). The planet, known as Proxima b, has not been observed as a transiting planet (Davenport et al 2016;Kipping et al 2017;Liu et al 2018;Blank et al 2018;Feliz et al 2019;Jenkins et al 2019) and the estimated geometric probability of a transit is about 1.5%, (Anglada-Escudé et al 2016). As a consequence, constraints can exclusively be set on the orbit semi-major axis and on the planet's revolution period, leaving mass, radius, and density of the planet to be assumed.…”
Section: Introductionmentioning
confidence: 66%
“…One kernel function that has been used to model stellar variability (specifically in stellar photometry, see Liu et al (2018); Littlefair et al (2017); Aigrain et al (2012Aigrain et al ( , 2015) is the squared exponential (SE) kernel ( 16).…”
Section: Squared Exponential Kernelmentioning
confidence: 99%
“…They found inconclusive evidence for transits of planet b, and they also found an additional transit candidate that was inconsistent with the transit window of Proxima b, perhaps indicating an additional planet. Liu et al (2018) used the Bright Star Survey Telescope at the Zhongshan Station in Antarctica to observe Proxima Centauri, conducting a 10-days long photometric monitoring campaign in 2016. This work also detected a transit-like signal consistent with the RV orbital parameters of planet b, but were unable to definitively confirm a transit of Proxima b.…”
Section: Introductionmentioning
confidence: 99%